Strategi Komunikasi Ferry Irwandi dalam Membangun Personal Branding di YouTube - Muhammad Adnan Faidh; Arfian Surya Suciramdhan; Muhamad Fauzan Kurniawan; Aldo Savero Zahran; Rian Firmansyah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to analyze Ferry Irwandi’s communication strategies in building personal branding on the YouTube platform. Ferry Irwandi was selected as a case study due to his success in constructing an authentic self-image through consistent spiritual and reflective narratives, as well as his strong engagement with a young adult audience. This research employs a qualitative approach using a case study method, involving video content observation, social media documentation, and in-depth interviews with both the subject and his audience. The findings reveal that Ferry Irwandi’s communication strategy is built upon four main pillars: narrative storytelling, message consistency, visual branding, and active audience engagement. These results highlight the significance of authentic narratives, consistent digital identity, and emotional interaction in developing a sustainable personal brand on social media.